Troponin testing in the emergency department: a longitudinal study to assess the impact and sustainability of decision support strategies. Issue 6 (12th March 2012) - Georgiou, Andrew; Lam, Mary; Allardice, Jane; Hart, Graeme K; Westbrook, Johanna I
Abstract : Aim: To evaluate the impact of decision support on the proportion of troponin I (cTnI) tests and associated costs over the period 2000–7 for patients presenting with chest pain in an emergency department (ED) setting. Methods: A longitudinal study using linked data for patients presenting with chest pain from the ED and laboratory information systems of a metropolitan teaching hospital in Melbourne, Australia. The study period was divided into a pre-intervention period (2000–2), which contained no decision support; an initial post period (2003–4) after the introduction of a quality improvement initiative (utilising a paper-based guideline, education, audit and feedback) about cTnI test ordering and the incorporation of the guideline as a decision support feature of the computerised provider order entry system; followed by a post-modification period (2005–7) after the electronic decision support feature was modified to allow clinicians to bypass viewing the complete guideline. Results: There was a significant fall in the proportion of cTnI tests ordered per patient presentation across the three periods—pre (2000–2), post (2003–4) and post-modification (2005–7)—from 7.3% to 4.1% and 2.8%, respectively. Analysis of costs showed significant reductions in the mean costs for cTnI tests per patient presentation from A9.28 to A8.54 and A8.18, respectively, which amounted to a modest saving of A13 251 since the initiation of decision support in 2003. Conclusions: Decision support systems are often part of multifaceted implementations undertaken over time. They require continuous monitoring and modifications to ensure optimal performance.